Environmental perception as a contribution to environmental education in protected area trails and creation of an interpretative itinerary - Risso, Luciene Cristina [UNESP]; Pascoeto, Jose Tadeu (Federal Univ Rio Grande, Inst Education, 2016)
The present article provides some considerations about environmental awareness and the creation of an interpretive script as a contribution to extensionism and environmental education in protected areas, directed to work with interpretative trails. The methodology adapted from the Alamo ( 1991) consisted of four phases: before trail, performing the trail with stops for dialogical explanation; stimulation of the senses, which aimed to awaken the contemplative capacity and internalization of environmental experiences and finally, the evaluation of the work on track and recommendation for teachers to continue the work that has been observed in the classroom. The result of these experiments was very positive. Visitors enjoy the scenic beauty of the park and said the trails in the woods provided entertainment and education.
Keywords: environmental awareness; environmental education; interpretive trails